PENGARUH PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) DAN GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Jasa Transportasi yang Terdaftar di BEI) - Sri Ayem; Suyanto Suyanto; Umi Wahidah (JEMMA (Journal of Economic, Management and Accounting), 2019)
This research aims to examine the effect of adopting International Financial Reporting Standards (IFRS) and Good Corporate Governance (GCG) on earnings management (case studies on transportation service companies listed on the Indonesian stock exchange. GCG in this study uses the audit committee proxy, institutional ownership, and Independent Commissioner, while earnings management in this study was measured by the Absolute discretionary accrual (ABSDA). This study used a population of transportation service companies listed on the Indonesia Stock Exchange. The data of this study were obtained from secondary data obtained from the Indonesia Stock Exchange in the form of Indonesian Capital Market Directory (ICMD) and the company's annual report from 2011-2017 The sampling method uses purposive sampling technique, the population that will be used as the research sample is a population that meets certain sample criteria. Companies that has the criteria of the research sample as many as 105 companies. To examine the effect of IFRS and good corporate governance on earnings management by using SPSS 16. The results showed that IFRS and Institutional Ownership affect earnings management. While the Audit Committee and Independent Commissioners have no effect on earnings management.